(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the outcome of compliance with the safe surgery protocol in cheiloplasty and palatoplasty procedures. Methodology: This is a cross-sectional, observational study carried out in a surgical center of a public teaching hospital in southern Brazil. The sample consisted of all surgeries performed between May and October 2021. The following study variables were evaluated: sex, age, type of surgery, type of anesthesia, surgery time, number of people in the operating room, completion of the checklist of safe surgery, completion of checklist steps and identified risk factors. Data analysis was performed using descriptive statistics. Results: 27 (100%) surgeries were performed during the study period, 59.3% of which were cheiloplasty and 40.7% were palatoplasty. There was a predominance of male patients (63%) in both procedures. Lack of beds (64%) and inadequate clinical status (36%) were the main reasons for surgical cancellation. There was a predominance of size I surgeries (77.8%) and it was observed that 74% of the surgeries had six to ten professionals in the room. The safe surgery protocol was performed in most of the surgical procedures investigated (74%), however, half of this amount was performed incompletely (37%). The greatest absence of checking occurred in the Time Out (59.2%). The study identified irregular completion of the surgical consent form in only 18.5% of the sample. Conclusion: even with failures in the execution of the safe surgery checklist, no adverse events were observed in the surgeries performed.